2011
DOI: 10.1097/wad.0b013e3182087dbc
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Nonpharmacological Treatment for Dementia-related Apathy

Abstract: A structured, nonpharmacological, short-term occupational therapy intervention is more useful than activities of the patients' own choice for improving apathy in patients with mild or moderate dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 43 publications
0
65
0
3
Order By: Relevance
“…), the Dementia Apathy Interview and Rating (DAIR) scale (Ferrero‐Arias et al . ), the Inventory to Assess Communication, Emotional Expression and Activity in Dementia (ICEA‐D) (Fischer‐Terworth & Probst ) and the Passivity in Dementia Scale (PDS) (Kolanowski et al . , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), the Dementia Apathy Interview and Rating (DAIR) scale (Ferrero‐Arias et al . ), the Inventory to Assess Communication, Emotional Expression and Activity in Dementia (ICEA‐D) (Fischer‐Terworth & Probst ) and the Passivity in Dementia Scale (PDS) (Kolanowski et al . , ).…”
Section: Resultsmentioning
confidence: 99%
“…Ferrero‐Arias et al . () intervened using a combination music, art, psychomotor activity and mime intervention. Niu et al .…”
Section: Resultsmentioning
confidence: 99%
“…They easily descend into a downward spiral of lack of activity, with those affected responding poorly to rehabilitation, due to absent motivation (Galynker et al, 1997). According to Ferrero-Arias et al (2011), a structured occupational therapeutic intervention for even a short period of time improves apathy in dementia patients and is much more beneficial than free use of the same amount of time by the patients in a nonstructured environment, but the effect is only useful in patient with mild or moderate dementia, and the effect in patients with severe apathy is even less important. Brodaty and Burns (2012) performed a systematic review on nonpharmacological intervention studies with outcomes relevant to apathy in dementia.…”
Section: Managementmentioning
confidence: 99%
“…Introducing old hobbies and games was successful in reducing disinhibition and inappropriate behaviors in FTD [69]. An apathy trial showed structured occupational therapy activities were more effective than “free time” in mixed group of AD, DLB, and vascular dementia patients, and music was felt to be most helpful [70]. A small but significant improvement in behavioral symptoms has been reported in a meta-analysis of occupational therapy trials using sensory stimulation [71].…”
Section: Assessmentmentioning
confidence: 99%